Strengthening Vocational Teachers' AI Literacy through NotebookLM Training: A Community-Based Initiative for Sustainable AI Integration in Vocational Education - Firahmi, Muhammad Wildi; Anisah, Hastin Umi; Wandary, Wimby; Nurhasanah, (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance vocational high school (SMK) teachers' AI literacy through NotebookLM training and to formulate practical strategies for the sustainable integration of artificial intelligence into vocational education. The program involved 35 SMK teachers and was implemented through a series of workshops, hands-on practice sessions, mentoring, and reflective discussions. Program effectiveness was evaluated using a one-group pretest-posttest design. Data were collected through validated pre-test and post-test instruments and analyzed using the Wilcoxon Signed-Rank Test and Normalized Gain (N-Gain) analysis. The results showed a statistically significant improvement in participants' understanding of NotebookLM, with mean post-test scores exceeding pre-test scores and an overall moderate N-Gain. The greatest learning gains were observed in participants' understanding and use of the Audio Overviews, Source Grounding, and Data Security features. Participants also reported increased confidence in integrating AI into instructional planning and classroom learning activities. Despite these positive outcomes, challenges related to digital infrastructure, varying levels of AI literacy, and teachers' readiness remained important considerations for wider implementation. These findings suggest that NotebookLM-based professional development can effectively enhance teachers' AI literacy while supporting the pedagogically meaningful integration of AI into vocational education. Continuous professional development, institutional support, equitable access to digital infrastructure, and collaboration with industry partners are essential to sustain AI adoption in vocational schools.